Effect of non-genetic factors on economic traits of Surti buffalo - Patel, A K; Tripathi, V N (The Indian Journal of Animal Sciences, 2012)
The effect of non-genetic radars, viz. season of calving, period of calving and parity was studied 011 Surti buffaloes,maintained at Central Cattle Breeding Farm (CCBF), Dhamrod (Gujurat). Analysis of 1099 lactation records revealedthat season of calving significanlly influenced the lactation yield (LY), 305-days or less lactation yield (305-LY), lactationlength (LL), dry period (DP), service period (SP) and calving interval (CI). Buffaloes commencing lactation in winterand summer (November to June) produced significantly higher LY, 305-LY and had a longer LL, whereas. buffaloescalving during rainy and autumn seasons (July to October) showed better reproductive performance (DP, SP and CI).Period of calving significantly influenced all the aforementioned traits. Higher productive and reproductive performanceswere obtained during third period (1985-87). Buffaloes in different parities differed significantly with respect to LY,305-L, DP, SP and CI. Surti buffaloes continuously improved their production performance up to fifth lactation andreproductive performance up to sixth lactation.